HOW TECHNOLOGY IS SHAPING OUR WORLD - Urakova Shakhlo; Tukhtamishov Shokhrukh (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article talks about how the technology is developing. it was mentioned that it is important that it is being updated to give us some conveniences. The evolution of technics and its impact on society have been subjects of significant scholarly inquiry. This literature review aims to examine a range of academic works that explore the evolution of technology and its profound influence on our world. By synthesizing key findings from various studies, this review sheds light on the transformative power of technology and the societal implications it entails.